Interpersonal relationships in medical consultations. – Comparing Sweden Swedish and Finland Swedish address practices - Catrin Norrby; Camilla Wide; Jan Lindström; Jenny Nilsson (Elsevier, 2022)
This article investigates how interpersonal relationships are expressed in medical consultations. In particular, we focus on how modes of address are used in the two national varieties of Swedish: Sweden Swedish and Finland Swedish, with the aim to compare the pragmatic routines in the two varieties. Thus the study contributes to the field of variational pragmatics, where national varieties of pluricentric languages are recognised as important research objects. Address practices are analysed in two comparable corpora of video recordings from Sweden and Finland using both a quantitative and a qualitative CA-inspired method. There are several differences between the data sets: the Sweden-Swedish data are characterised by exclusive use of the informal T pronoun (du ‘you’) and an overall higher frequency of direct address compared to the Finland-Swedish data. In some medical consultations in the Finland-Swedish data the formal V pronoun (ni) is used. The qualitative analysis confirms these differences and the tendency is that the Sweden-Swedish medical consultations are more informal than the Finland-Swedish ones, which are characterised by more formality and maintenance of social distance between the interlocutors. The different pragmatic orientations at the micro level of communication can also be related to socio-cultural preferences at the macro level in society – the development towards greater informality and intimate language is more pronounced in Sweden than in Finland.